Study on the optimal setting of architectural reference area and the number of classrooms of middle and primary-school classroom by neural network - Nam, Pak Jong (International Journal of Architecture and Urbanism, 2025)
Recently, the architectural and design sector of the school has been very concerned with the rational setting of classroom area in accordance with the actual requirements of changing from traditional classroom structure to multifunctional classroom structure with intensive modern educational technology. In this paper, we consider how to construct the optimal model for the architectural reference area setting and the determination of classroom number in middle- and primary-schools using the principle of ANN and to verify the effectiveness of the proposed optimal model by means of an application example.